KARAKTERISTIK BATU BATA TANPA PEMBAKARAN TERBUAT DARI ABU SEKAM PADI DAN SERBUK BATU TABAS - Sudarsana, I Ketut; Made Budiwati, Ida Ayu; Angga Wijaya, Yohanes (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011, 2012)
This research was conducted to determine the characteristics of the brick compressive strength and water absorption. The bricks are made by using waste rice husk ash and rock-tabas powder which are added to cement as a glue and mixed with clay and they are left dry without firing. A total of five kinds of mixtures were made with a proportion of total rice husk ash and rock-tabas powder of 30%, 60% of clay and cement as much as 10% mixed with weight ratio. Variations of composition of rice husk ash and rock-tabas powder were made using ratios of 0%: 30%, 7.5%: 22.5%; 15%: 15%, 22.5%: 7.5%, and 30%: 0 %. The samples used are in the form of cubes with a size of 6x6x6 cm. Six-cubes were made form each mixture where 3 of them were used for compressive strength test and the other 3 for water absorption test. Tests conducted at 14 and 28 days. The result showed that the highest compressive strength of bricks without firing was 22.90 kg/cm2 obtained from the mixture I with the percentage of rice husk ash and pulverized tabas of 30%:0% at 28 days, while the lowest water absorption is at 44.03% gained from bricks of mixture V in which the ratio between rice husk ash and rock-tabas powder was 0%:30% at 28 days.
Keywords: rice husk ash, rock-tabas powder, unburnt brick, compressive strength, water absorption.